2018
DOI: 10.1089/neu.2017.5538
|View full text |Cite
|
Sign up to set email alerts
|

Variability of Leg Kinematics during Overground Walking in Persons with Chronic Incomplete Spinal Cord Injury

Abstract: Incomplete spinal cord injury (iSCI) often leads to partial disruption of spinal pathways that are important for motor control of walking. Persons with iSCI present with deficits in walking ability in part because of inconsistent leg kinematics during stepping. Although kinematic variability is important for normal walking, growing evidence indicates that excessive variability may limit walking ability and increase reliance on assistive devices (AD) after iSCI. The purpose of this study was to assess the effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 56 publications
1
9
0
1
Order By: Relevance
“…The non-significant association between the composite spatial and temporal asymmetry indices (Figure 4b) may therefore be driven by unequal deficits in phase accuracy between spatial and temporal domains rather than differences in step to step consistency. This suggests corrupt sensorimotor control underlying the reproducibility of consistent motor coordination during walking, supplementing prior reports of increased kinematic variability within a single limb [6]. Thus, even though accuracy maybe differentially impaired between space and time domains, consistency from step to step appears equally impaired.…”
Section: Interlimb Coordination Is Impaired After Iscisupporting
confidence: 71%
See 3 more Smart Citations
“…The non-significant association between the composite spatial and temporal asymmetry indices (Figure 4b) may therefore be driven by unequal deficits in phase accuracy between spatial and temporal domains rather than differences in step to step consistency. This suggests corrupt sensorimotor control underlying the reproducibility of consistent motor coordination during walking, supplementing prior reports of increased kinematic variability within a single limb [6]. Thus, even though accuracy maybe differentially impaired between space and time domains, consistency from step to step appears equally impaired.…”
Section: Interlimb Coordination Is Impaired After Iscisupporting
confidence: 71%
“…Specifically, we tested for correlations between spatial and temporal AI, GCI, and PCI, as well as, AI and walking assessment scores (10MWT, 6MWT, and SCI-FAI) in iSCI subjects. Since a prior study showed persons with iSCI who required a "walker" for ambulation had greater intralimb coordination deficits as compared to those who used a less restrictive AD (i.e., cane, loftstrands) [6], we predicted a similar result with interlimb coordination. Thus, we stratified our iSCI subjects into those who used a "walker" (N = 7) for ambulation and those who did not (N = 9).…”
Section: Statistical Analysesmentioning
confidence: 86%
See 2 more Smart Citations
“…In addition to improvements in walking speed, participation in 3 days of MST was associated with significant increases in stride frequency (cadence) and length. Gait kinematics associated with walking impairments in persons with SCI have been reported extensively ( Field-Fote and Tepavac, 2002 ; Pepin et al, 2003 ; Nooijen et al, 2009 ; Awai and Curt, 2014 ; Sohn et al, 2018 ; Ardestani et al, 2019 ). Both stride frequency and stride length are coupled to walking speed modulation in non-injured adults ( van Hedel et al, 2006 ).…”
Section: Discussionmentioning
confidence: 99%